2013
DOI: 10.1002/jrs.4280
|View full text |Cite
|
Sign up to set email alerts
|

Single‐shot thermometry using fiber‐based picosecond coherent anti‐stokes Raman scattering (CARS) spectroscopy

Abstract: Coherent anti‐Stokes Raman scattering (CARS)‐spectroscopy‐based thermometry techniques developed for laboratory flames face a stiff challenge when implemented in practical combustion environments such as engine test facilities. In addition to limited optical access, the harsh environments associated with these test facilities (i.e. uncontrolled humidity, vibration, and large thermal gradients) often restrict the operation of sensitive laser systems. To circumvent this problem, we have developed a fiber‐based, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Because of quadratic and higher order dependences on excitation-beam power density, laser sources with sub-ns pulse duration are usually required for nonlinear spectroscopic measurements with high signal-to-noise ratio, especially for acquiring spatially and temporally resolved one-or two-dimensional data. Furthermore, sub-ns pulses have also been shown to improve the peak power available for nonlinear spectroscopic approaches when fiberbased laser delivery is utilized [5]. Fiber coupling is potentially important for propulsion devices with limited optical access and for measurements in harsh operating conditions.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Because of quadratic and higher order dependences on excitation-beam power density, laser sources with sub-ns pulse duration are usually required for nonlinear spectroscopic measurements with high signal-to-noise ratio, especially for acquiring spatially and temporally resolved one-or two-dimensional data. Furthermore, sub-ns pulses have also been shown to improve the peak power available for nonlinear spectroscopic approaches when fiberbased laser delivery is utilized [5]. Fiber coupling is potentially important for propulsion devices with limited optical access and for measurements in harsh operating conditions.…”
mentioning
confidence: 98%
“…The availability of a high-energy, sub-ns burst-mode laser would allow sufficient energy for pumping frequency-conversion devices and be suitable for fiber-based delivery. For example, it was shown that 100 ps pulses are optimal for fiber coupling in the case of single-shot CARS thermometry [5]. Although the 100 ps pulse duration is optimal, there is a lack of high-energy ps burst-mode lasers, and commercially available systems have repetition rates below 50 Hz.…”
mentioning
confidence: 99%
See 3 more Smart Citations